2010
DOI: 10.1111/j.1365-2362.2010.02435.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysing cell‐free plasma DNA and SLE disease activity

Abstract: The presented data seem to exclude measuring free plasma DNA as an inexpensive, simple and quick tool to assess disease activity in patients with SLE. Further studies on a larger patient population would be needed to confirm our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
33
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 14 publications
7
33
1
Order By: Relevance
“…Isolation of DNA and ICs and treatment of plasma with nucleases and proteases DNA was isolated from SLE plasma using a DNA Isolation Kit (Roche), as described previously (10). The final A260/A280 for all DNA preparations was .1.8.…”
Section: Cell Isolationmentioning
confidence: 99%
See 2 more Smart Citations
“…Isolation of DNA and ICs and treatment of plasma with nucleases and proteases DNA was isolated from SLE plasma using a DNA Isolation Kit (Roche), as described previously (10). The final A260/A280 for all DNA preparations was .1.8.…”
Section: Cell Isolationmentioning
confidence: 99%
“…DNA-Ab binding and subsequent events, such as complement activation, IC deposition, and cytokine release, take place in the circulation of SLE patients (10). Accumulating studies showed that circulating DNAcontaining ICs could activate human plasmacytoid dendritic cells to induce type I IFN responses and, thus, are involved in SLE pathogenesis (11)(12)(13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While some of them reported correlation of cfDNA levels with disease activity or relationship with unfavorable outcome in situations like systemic sclerosis, experimental pulmonary thromboembolism, severe sepsis or intensive care unit patients; such a study done in SLE patients revealed not very promising results [22][23][24][25][26]. Atamaniuk et al [26] in their research measuring the levels of circulating DNA as a potential tool to assess and to predict disease activity in patients with SLE indicated that cfD-NA plasma levels in patients with SLE were significantly increased. The authors stated that especially apoptosis and necrosis would lead to an increase in measurable free plasma DNA, however they found no correlation between cfDNA levels and SLE activity.…”
Section: Discussionmentioning
confidence: 99%
“…In the late 1990s (after the landmark papers by Chen et al [12] and Nawroz et al [13] were published) this observation initiated a surge of papers confirming and extending the results described by Leon et al Unfortunately, it became clear very soon that the increase in cfDNA in tumor patients is not specific and that many factors/diseases lead to the higher quantity of cfDNA (see chapter "The Biology of CNAPS"). When cfDNA had been quantified it was shown that the amount is increased in a variety of different conditions such as myocardial infarction [14], cardiac arrest [15], exhaustive exercise [16][17][18], in patients with systemic lupus erythematosis [19], in older humans [20], in febrile patients [21], in children on peritoneal dialysis [22], in patients with obstructive sleep apnea [23], patients with chronic kidney disease [24], patients with severe sepsis or septic shock [25], in trauma [26] and burn patients [27] (chapter "CNAPS and General Medicine"). In an attempt to differentiate lung cancer patients from a control population according to their sputum cfDNA it was demonstrated that the amount of cfDNA was related to the severity of the inflammatory processes but not the presence of lung cancer [28].…”
Section: Dna Quantification/dna Integritymentioning
confidence: 99%